ABC‐Type meso‐Triaryl‐Substituted Subporphyrins. Issue 19 (27th May 2014) - Yoshida, Kota; Mori, Hirotaka; Tanaka, Takayuki; Mori, Tadashi; Osuka, Atsuhiro
Abstract: ABC‐Type subporphyrins5a –5h, which bear three different meso ‐aryl substituents, were rationally synthesized by condensation of AB‐type tripyrranes and aroyl chlorides. ABC‐Type subporphyrins5i and5j were synthesized by Pd‐catalyzed amination reaction of 4‐bromophenyl subporphyrins5e and5h, respectively. Comparative studies on these ABC‐type subporphyrins with A3 ‐type subporphyrins and A2 B‐type subporphyrins revealed that substituent effects are mostly simple superpositions of individual substituents but cooperative effects are recognized for subporphyrins which bear both electron‐donating and electron‐withdrawing substituents. Despite extensive attempts, enantiomeric separation of B‐methoxy ABC‐type subporphyrins was unsuccessful, whereas B‐phenylated ABC‐type subporphyrins were separated to pure enantiomers. Separated enantiomers showed weak but distinct CD signals reflecting the chiral clockwise/anticlockwise arrangements of the meso ‐aryl substituents. These results suggest facile racemization through SN 1‐type heterolysis of the B–OMe bond in solution. Abstract : ABC‐Type meso ‐triaryl‐substituted subporphyrins were rationally synthesized. Cooperative substituent effects are noted for donor‐acceptor‐type subporphyrins. Although the chiral resolution has not been successful for B‐methoxy ABC‐type subporphyrins, the enantiomers of some B‐phenyl subporphyrins have been resolved by using chiral HPLC.